2021
DOI: 10.3390/su13052563
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Poverty by Municipalities in the Context of Population Ageing—The Case of Małopolskie Voivodeship

Abstract: This article undertakes the research problem of the assessment of the significance of poverty as a social challenge for local self-government units, and the differences in the assessment of the incidence of this phenomenon depending on the type of municipality. The authors also analyse the relationships between the ageing of the population and the assessment of the extent of poverty by municipalities. It must be pointed out that the undertaken problem has not been a subject of in-depth analysis thus far. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For regions with a high degree of aging, Cwiek recommended that relevant sectors realize the development potential of the silver economy [8]. Youn found that female participants who transitioned to poverty and remained in poverty showed an increased odds of showing weakness during the follow-up year, but no significant results were found among male participants [9].…”
Section: Introductionmentioning
confidence: 99%
“…For regions with a high degree of aging, Cwiek recommended that relevant sectors realize the development potential of the silver economy [8]. Youn found that female participants who transitioned to poverty and remained in poverty showed an increased odds of showing weakness during the follow-up year, but no significant results were found among male participants [9].…”
Section: Introductionmentioning
confidence: 99%